THE INFLUENCE OF THE SOCIAL ENVIRONMENT IN PRE-SCHOOL ON EARLY CHILDHOOD DEVELOPMENT - Al Mufidah, Wida; Damayani Twinsari Maningtyas, Rosyi; Iriyanto, Tomas (Proceeding of International Conference on Multidisciplinary Research, 2024)
This article aims to investigate the influence of the social environment in early childhood education on early childhood development. Early childhood education (ECE) is a critical stage in children's development, where the social environment can play an important role in shaping their potential and skills. This study used a qualitative approach by collecting data through participatory observation and interviews with teachers, parents and children in PAUD institutions. The data collected was analysis using thematic analysis method to identify emerging themes and patterns related to the influence of social environment. The results show that the social environment in PAUD has a significant impact on early childhood development. Interactions with peers and teachers can improve children's social and cognitive abilities, developing speaking, sharing, cooperation and problem-solving skills. In addition, a supportive environment, including positive relationships between parents and children, also contributes to children's emotional development and self-confidence. In addition, an environment rich in stimulative activities such as games, nature exploration, art and music can stimulate a child's sensory and motor development. An environment that provides opportunities to interact with diverse objects and materials can also enhance children's creativity and imagination. However, the study also found that less supportive social environments, such as family conflict or unsafe neighbourhoods, can have negative effects on early childhood development. These factors can affect children's emotional and psychological well-being, and hinder their ability to learn and interact socially. In order to optimize the influence of the social environment in ECE, there needs to be close cooperation between parents, teachers and the local community. Through joint efforts, a positive, inclusive and supportive social environment can be built, creating optimal opportunities for early childhood development.